Spiritual Needs of First Nations, Métis and Inuit Foster Parents - Brown, Jason; Mehta, Nisha; Skrodzki, Donna; Gerritts, Julie; Ivanova, Viktoria (First Peoples Child & Family Review)

(untitled) (First Nations Child and Family Caring Society of Canada, 2013)
Aboriginal children are overrepresented in foster care and more Aboriginal foster parents are needed. A randomized group of licensed First Nations, Métis and Inuit foster parents in a Canadian jurisdiction were asked about their spiritual needs to foster. In response to the question “what do you need spiritually to foster?” there were 55 unique responses that were grouped by participants into five concepts including: religion, practice, integration, sharing and contentment. These results were compared and contrasted with the existing fostering literature.